Broad Band Electromagnetic Interference (EMI) Shielding Properties of Polyaniline/ Polyvinyl Alcohal/ Fly Ash/ MnO2 Free Standing Films - M, Revana siddappa; SiddalingaSwamy, D; Raghavendra, S.C.; Ravikiran, Y.T. (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Microwave absorbing material (MAM) is a kind of functional material that can absorb electromagnetic wave effectively and convert electromagnetic energy into heat or make electromagnetic wave disappear by interference. These types of materials are gaining much attention in the field of civil and military applications. The present work is the report of our effort in studying the EMI-Shielding properties of conducting polyaniline (PANI) and their composites. The wet dark green precipitate and varied weight percentage (wt %) of cenosphere particles were transferred directly to the 5% polyvinyl alcohol (PVA) solution. The resulting mixture was stirred continuously for 1 hour for homogeneous distribution of the particles. The mixture was poured on to the glass plate and allowed to dry at room temperature to get freestanding PANI/FA/MnO2/PVA polymer matrix. The electromagnetic wave absorption, reflection and EMI Shielding Effectiveness (EMI SE) of the composites has been measured at X-band (8-12 GHz) micro wave frequencies. The experimental results indicate that the absorption dominated EMI SE of the composites is influenced by the fly ash weight percentage. The study suggests the prospects of the composites as effective shielding materials for a broad range of micro wave frequency.